2011
DOI: 10.1111/j.1746-1561.2010.00577.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Adolescent Male Body Image Dissatisfaction: Implications for Negative Health Practices and Consequences for School Health From a Regionally Representative Sample

Abstract: Educators and school districts should consider the confluence of psychosocial variables affecting body image and adolescent male health risk behaviors based on a statistically sound predictive model as provided by the ABISS. Targeted programming to enhance body image and address teasing/bullying behaviors is strongly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 51 publications
1
26
0
1
Order By: Relevance
“…More recent research has demonstrated that body image concerns are no longer confined to Western populations, with numerous studies showing the emergence of body dissatisfaction among male and female adolescents in Asia (e.g., Grammas & Schwartz, 2009;Jung et al, 2009;Leone et al, 2011;Mellor et al, 2013;Wardle, Haase, & Steptoe, 2006), and an increase in eating disorders and other body change strategies across a number of Asian cultures (Jung et al, 2009;Jung & Forbes, 2006Wardle et al, 2006;Xu et al, 2010). In addition, there is growing evidence Asian adolescent males are concerned about lean muscularity (Mintz & Kashubeck, 1999;Thianthai, 2008;Watt & Ricciardelli, 2012;Xu et al, 2010).…”
Section: Male Body Dissatisfaction Across Western and Asian Culturesmentioning
confidence: 99%
“…More recent research has demonstrated that body image concerns are no longer confined to Western populations, with numerous studies showing the emergence of body dissatisfaction among male and female adolescents in Asia (e.g., Grammas & Schwartz, 2009;Jung et al, 2009;Leone et al, 2011;Mellor et al, 2013;Wardle, Haase, & Steptoe, 2006), and an increase in eating disorders and other body change strategies across a number of Asian cultures (Jung et al, 2009;Jung & Forbes, 2006Wardle et al, 2006;Xu et al, 2010). In addition, there is growing evidence Asian adolescent males are concerned about lean muscularity (Mintz & Kashubeck, 1999;Thianthai, 2008;Watt & Ricciardelli, 2012;Xu et al, 2010).…”
Section: Male Body Dissatisfaction Across Western and Asian Culturesmentioning
confidence: 99%
“…Whereas previous studies on smoking and weight control have focused primarily on adolescent girls, recent research suggests that both sexes are susceptible to weight concerns as they pertain to smoking . This is consistent with studies that have documented that adolescent boys are increasingly concerned about their weight and body image . Instead of consuming fruits and vegetables to promote healthy weight, there is a widespread belief that smoking helps with weight control .…”
mentioning
confidence: 54%
“…concerned about their weight and body image. 7,8 Instead of consuming fruits and vegetables to promote healthy weight, 9 there is a widespread belief that smoking helps with weight control. 6,10,11 Although adolescents may smoke to lose weight, 6,12 their efforts to lose weight are defeated by early adulthood.…”
mentioning
confidence: 99%
“…The dynamic relationship of these three factors gives a direct effect on the development of teen body image (Leone, et al, 2011). Santrock (2007) says along with the physical development that occurs in early adolescence, one of the psychological aspects that occur is the adolescent to be very concerned about his body (preoccupation) and develop an individual image of the appearance of his body.…”
Section: Results Of Research By Correlation Analysismentioning
confidence: 99%